Impacto de la agricultura de precisión en la sostenibilidad ambiental en el Ecuador - Salvatierra Velasco, Máximo Alfonso (2025)
Precision agriculture optimizes the application of technologies in agricultural production, however, its adoption faces limitations of high costs or limited access to financing. For this reason, to mitigate the environmental impact, it is essential to implement innovative strategies that improve efficiency in resource management, strengthen crop resilience and promote more sustainable management of agricultural ecosystems. The general objective of this research is based on evaluating the impact of precision agriculture on environmental sustainability in Ecuador. The methodology used was based on the collection of information from current scientific research articles, virtual libraries and websites. Regarding the results, they indicated that among the precision agriculture practices, the use of technologies such as advanced chlorophyll, humidity and nutrient sensors, the use of drones for fumigation, intelligent irrigation systems, vegetation index and variable application of inputs, optimize the management of resources, nutrients and reduce environmental impact. In addition, the integration of preventive, biological and chemical techniques allows for more effective control of pests and diseases, preserving the stability of agroecosystems. In conclusion, these tools reduce the excessive use of agrochemicals, and at the same time, allow for the conservation of soil and water. Also, the use of slow-release fertilizers and phytosanitary products have improved productive efficiency and long-term agricultural sustainability, guaranteeing a balance between profitability and environmental care.